2022
DOI: 10.1039/d2nr02026b
|View full text |Cite
|
Sign up to set email alerts
|

An inflammation-targeted nanoparticle with bacteria forced release of polymyxin B for pneumonia therapy

Abstract: The epidemic of multidrug-resistant gram-negative bacteria is an ever-growing global concern. Polymyxin B (PMB), a kind of “old fashioned” antibiotic, has been revived in clinical practice and mainly used as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…This result showed that D‐J‐1 could exert potent in vivo antimicrobial activity in the body of an animal model. Due to bacterial infections that could trigger the inflammation response and impede the wound healing process on the body surface or in vivo, [ 21 ] the antimicrobial activity would be an advantage of D‐J‐1 hydrogel and expand its applications.…”
Section: Resultsmentioning
confidence: 99%
“…This result showed that D‐J‐1 could exert potent in vivo antimicrobial activity in the body of an animal model. Due to bacterial infections that could trigger the inflammation response and impede the wound healing process on the body surface or in vivo, [ 21 ] the antimicrobial activity would be an advantage of D‐J‐1 hydrogel and expand its applications.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, by reducing the positive charge of PMB, PMB-HA nanoparticles reduce cellular damage as well as histological toxicity, thus improving cellular and biological safety. This intelligent delivery system provides a new approach for the resurrection of PMB in the treatment of bacterial inflammatory diseases [ 115 ].…”
Section: Bioactive Nanoparticles For the Treatment Of Bacterial Infec...mentioning
confidence: 99%
“… Schematic illustration of the construction of inflammation-targeted smart nanoparticles PMB-HA, together with the molecular mechanism of their bacteria-triggered PMB-forced-release ability to precisely kill the pneumonia bacteria with outstanding biosafety. Modified and reproduced with permission from the Royal Society of Chemistry [ 115 ]. …”
Section: Figurementioning
confidence: 99%
“…The aim of this study was therefore to develop a delivery system protecting polypeptide antibiotics against enzymatic degradation and enabling their transport across the mucus gel layer by the design of polyphosphate NPs. As a model polypeptide antibiotic polymyxin B (PMB) being used for the treatment of multidrug-resistant (MDR) infections in the eye, ear, skin, and bloodstream was chosen because of its cationic charge and since it can be administrated just via intravenous, intramuscular, pulmonary, intrathecal, and topical routes. , Furthermore, various studies have already shown that PMB can be efficiently complexed with anionic polymers forming NPs through electrostatic interactions. , The formation of stable complexes between PMB and polyphosphate (PP) should thus be feasible and might enable us to form NPs even without any cationic polymeric excipients that pose a safety concern. Furthermore, a protective effect of the peptide toward enzymatic degradation should be provided.…”
Section: Introductionmentioning
confidence: 99%